A glimpse of ephemeral subduction zone processes from Simberi Island, Papua New Guinea - Mcinnes, Brent I. A.; University of Ottawa (Canada) (1992)
Simberi Island is an eroded Pliocene alkaline volcano, the oldest in the Pliocene to Holocene Tabar-Lihir-Tanga-Feni (TLTF) island arc. These islands are derived from partial melting of subduction-modified mantle at $>$60 km depth along extensional, pull-apart structures. Explosive volcanism has brought samples of the mantle wedge to the surface. Within these samples are sulphate-, carbonate-, hydrous-, alkali-rich aluminosilicate glasses which represent quenched slab-derived magmas (SCHARM). SCHARM reacts with mantle peridotite to create a vertically zoned mantle wedge consisting of phlogopite-clinopyroxenite at P $>$ 30 kbar and amphibole-clinopyroxenite at 21 to 30 kbar at 930-1080$\sp\circ$C. Metasomatism of the mantle wedge by SCHARM controls the mineralogical, chemical and isotopic composition of TLTF arc volcanics. The presence of sulphate within SCHARM indicates a high intrinsic oxygen fugacity of FMQ + 4.
Oxidative metasomatism of the mantle wedge by SCHARM is responsible for high $\rm Fe\sb2O\sb3$/FeO ratios in the lavas, the early appearance of magnetite on the liquidus and the crystallization of a sulphate-bearing feldspathoidal mineral (ha uyne) in the TLTF lavas. Titanium depletion in the rocks of the TLTF arc is accounted for by the low initial solubility of Ti in SCHARM, coupled with the strong partitioning of Ti into phlogopite at high fo$\sb2.$ Enhanced solubility of sulphur in high fO$\sb2$ melts, caused destabilization of mantle sulfides and concomitant enrichment of chalcophile Au and Cu in volatile-rich, mantle-derived melts, and may be a significant factor in the development of volcanic-hosted Au-Cu deposits in the arc.
Enrichments of large ion lithophile elements and rare-earth element in basanites and alkali basalts are also due to SCHARM contamination. Negative Ce and positive Eu anomalies in Simberi basalts are produced by partial melting of feldspathic minerals in subducted, seawater altered mid-ocean ridge basalt (MORB), at the basalt-eclogite transition zone in the mantle. Eutectic melting constraints indicate that SCHARM could be derived during the melting of scapolite, produced by prograde metamorphic reactions between MORB plagioclase and low temperature secondary minerals (calcite, gypsum) in the subducting slab. Metasomatic replacement of forsteritic olivine $\rm(\delta\sp{18}O=5\perthous)$ by high $\rm\delta\sp{18}O$ SCHARM produces $\sp{18}$O-enriched sodian diopside and magnetite $\rm(\delta\sp{18}O$ = 6.3-6.8$\perthous)$ in Simberi basanites. Isotopic disequilibrium exists because of the short $(<$6 Ma) residence time of SCHARM in the mantle.
(UnM)AAINN75082
Source: Dissertation Abstracts International, Volume: 54-01, Section: B, page: 0134.
Directeur: E. Cameron.
Thesis (Ph.D.)--University of Ottawa (Canada), 1992.
Microfiche.
Keywords: Geology